2013
DOI: 10.1159/000354234
|View full text |Cite
|
Sign up to set email alerts
|

Live-Supervision: Vom Einwegspiegel zur videobasierten Online-Supervision

Abstract: Live-Supervision ermöglicht dem Supervisor, Einblicke in eine laufende Therapiesitzung zu erhalten und in diese beratend einzugreifen. Die direkte Rückmeldung des Supervisors an den Supervisanden stellt dabei ein wichtiges Unterscheidungsmerkmal zu nachträglichen Supervisionsformen dar. In den letzten 60 Jahren wurden verschiedene Formen der Live-Supervision entwickelt, die im Rahmen dieser Arbeit in Hinblick auf ihre Praktikabilität, Akzeptanz und Effektivität diskutiert werden. Aufgrund der vielen Vorteile v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Therefore, the evaluations of different perspectives on therapeutic alliance and therapist competence would also be interesting and should be considered in future studies. However, in two previous studies, we found a positive evaluation of BITE supervision by therapists and patients by considering quantitative (Jakob et al, 2013) and qualitative data .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, the evaluations of different perspectives on therapeutic alliance and therapist competence would also be interesting and should be considered in future studies. However, in two previous studies, we found a positive evaluation of BITE supervision by therapists and patients by considering quantitative (Jakob et al, 2013) and qualitative data .…”
Section: Discussionmentioning
confidence: 62%
“…Various live supervision formats have been developed, including the phone-in (i.e., the supervisor is able to contact the trainee via the telephone), knock-on-the-door (i.e., the supervisor knocks on the door and provides the trainee with instructions outside of the therapy room), bug-in-the-ear (i.e., the supervisor provides verbal instructions via an earpiece) and bug-in-the-eye (BITE, i.e., the supervisor provides written instructions via a visual display [ Figure 1]) techniques. Live supervision has many advantages over delayed forms of supervision (e.g., retrospectively discussing case reports or listening to audiotapes or videotapes [Jakob, Weck, & Bohus, 2013]). Live supervision enables immediate feedback to be provided to the trainee, which might be more useful than delayed supervisory interventions (Rousmaniere & Frederickson, 2013).…”
mentioning
confidence: 99%
“…More explorative studies may be needed to identify optimal methods for skills training as well as methods for implementing skills in clinical practice. Live supervision may for example, provide a context in which the distance from learning and practice is much shorter than in delayed supervision (F. Weck et al, 2016;Jakob et al, 2013). In the current study, the most commonly chosen item for development items from the CTS-R was Guided Discovery which was chosen by four participants.…”
Section: Discussionmentioning
confidence: 99%
“…Stein and colleagues (1975) found that supervisors perceived clients’ disorders as more severe when listening to audiotapes of trainees’ assessments than when listening to trainees’ subjective reports of the same assessments. This discrepancy may be attributable to a tendency of novice trainees to focus more on self-monitoring than on client presentation (Jakob, Weck, & Bohus, 2013). It is also impossible for trainees to recall all salient aspects of a treatment session even when aided by session notes (Haggerty & Hilsenroth, 2011), and trainees may lack sensitivity to more subtle clinically relevant information, such as facial expressions, mannerisms, tone of voice, interruptions, and so forth.…”
Section: Observation Methods In Supervisionmentioning
confidence: 99%
“…Using the same methods as Jakob et al (2013), assessment of the trainee and client's satisfaction with BITE showed that both experienced it to be acceptable and undisruptive to the therapeutic alliance and in general. The trainee in particular strongly endorsed that BITE improved the effectiveness of her work.…”
Section: Uncontrolled Studiesmentioning
confidence: 99%